FORUM MŁODYCHBacterial ascending mediastinitis following diagnostic pleuroscopy in a patient with pleural tuberculosis - Jabłoński, Sławomir; Misiak, Piotr (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2012)
Descending necrotizing mediastinitis is an emergency surgical condition with a high mortality rate. The inflammatory process spreads downwards along the neck fascial space from primary infection foci from the oro-pharynx. Usually mediastinitis of bacterial etiology is polymicrobial in nature and presents with an acute course. Mediastinitis of specific etiology, characterized by chronic course and causing mediastinal fibrosis, is rare. The study presents an atypical case of iatrogenic acute mediastinitis, which developed in an ascending mechanism in a patient after diagnostic left pleuroscopy performed due to parietal pleural pathology with accompanying pleural effusion. Histopathological examination of the pleural specimens revealed pleural tuberculosis.